Screening of native plant species for phytoremediation potential in Pb-Zn mines in Iran - M Kazemi (Environmental Resources Research, 2021)
Mining activity is one of the major sources of heavy metal pollution of soil. Most mines are abandoned without any remediation and cause contamination of soil and water. Phytoremediation is an environment-friendly technology for the remediation of contaminated sites. In this work, native plant species were identified that can tolerate high concentrations of heavy metals and are useful for phytoremediation in an abandoned Pb-Zn mine in the north of Iran. Twelve plant species and the corresponding soils were collected and analyzed for As, Cd, Co, Cr, Cu, Mo, Pb, Sb, Ni and Zn contents using inductively coupled plasma mass spectroscopy (ICP-MS). In order to measure the bioavailability of heavy metals for plants uptake, DTPA extraction of heavy metals were determined. Then, the physiochemical characteristics of the soil samples were measured and the translocation factors (TFs) and bio-concentration factors (BFs) were determined. The soil samples were alkaline, and exhibited low electrical conductivity, high cation-exchange capacity, moderate organic carbon content, and clay loam texture. All samples exceeded the soil toxicity thresholds for AS, Cd, Pb, Sb, and Zn. The results indicate that Stachys byzantina has the ability to accumulate significant amounts of Pb in its shoot. The average concentrations of Pb in the soil, shoot, and root were 15472mg kg-1, 1797 mg kg-1, and 371 mg kg-1, respectively, with TF value of 4.8 and BF value of 0.1. Therefore, S. byzantina may have the potential to function as a Pb hyper-accumulator and merits further investigation.